1993
DOI: 10.1021/ac00052a027
|View full text |Cite
|
Sign up to set email alerts
|

Determination of carbohydrates by capillary zone electrophoresis with amperometric detection at a copper microelectrode

Abstract: Capillary zone electrophoresis (CZE) was employed to separate sugars according to their electrophoretic mobilities In strong alkaline solutions (pH ca. 13). Saccharide zones were monitored electrochemlcally using amperometric detection at a constant potential, 0.6 V (vs Ag/AgCI), with a cylindrical copper wire electrode (25 pm In diameter). The Cu-wlre microelectrode In strong basic solutions had electrochemical behavior similar to that of Cu electrodes with larger dimensions and appeared to show no deteriorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(140 citation statements)
references
References 39 publications
8
131
0
1
Order By: Relevance
“…The separated carbohydrates are sometimes detected by electrochemical detection (ECD) or PAD on a metal electrode. 144,145 The detection limit of these methods can reach femtomole levels. Alternatively, indirect detection can also be employed, using various fluorescent dyes including fluorescein and coumarins for sensitive detection.…”
Section: ·2 Separation Of Carbohydrates As Anions Using a Strongmentioning
confidence: 99%
“…The separated carbohydrates are sometimes detected by electrochemical detection (ECD) or PAD on a metal electrode. 144,145 The detection limit of these methods can reach femtomole levels. Alternatively, indirect detection can also be employed, using various fluorescent dyes including fluorescein and coumarins for sensitive detection.…”
Section: ·2 Separation Of Carbohydrates As Anions Using a Strongmentioning
confidence: 99%
“…Sistemas mais sofisticados envolvendo a remoção 40,52,157 , enzimas e proteínas [160][161][162] , co-fatores 163 , nucleotídeos e similares [164][165][166] , ácidos policarboxílicos 167 , hormônios 168 , bem como outros metabólitos, como ácido úrico 169 [197][198][199][200][201] . A ED também é bastante apropriada em separações eletroforéticas em meio não-aquoso (NACE), uma vez que a maioria dos solventes utilizados absorve fortemente na região do UV, o que dificulta as medidas fotométricas.…”
Section: Detecção Amperométrica (Ad)unclassified
“…Since most sugars have a pK a value between 12 and 13, a high pH of the electrolyte is required for their separation [15][16][17][18]. The conductivity of the medium increases with the pH and the resulting high electrophoretic currents are accompanied with baseline instabilities and low signal-to-noise ratios with indirect UV detection.…”
Section: Noise Reduction By Instrumental Optimizationmentioning
confidence: 99%
“…It was found that a number of di-and trisaccharides as well as aldonic acids still could not be derivatized successfully [14]. (c) With an electrochemical detector, underivatized sugars can be detected sensitively by a pulsedpotential technique with a gold electrode [15] or at a constant detection potential with copperbased electrodes [16,17]. A high pH (12)(13) solution is necessary for the separation as well as for the detection.…”
Section: Introductionmentioning
confidence: 99%